2018
DOI: 10.1177/0961203318768880
|View full text |Cite
|
Sign up to set email alerts
|

Increased flexibility, pain reduction and unaltered levels of IL-10 and CD11b + lymphocytes in patients with systemic lupus erythematosus were associated with kinesiotherapy

Abstract: The effect of physical activity on the immune system is still poorly understood in cases of systemic lupus erythematosus (SLE). Therefore, our aim was to investigate differences in the serum levels of cytokines (IL-2, IL-5, IL-6, IL-8, IL-10 and TNF-α) and the numbers of CD11b + and CXCR2 + neutrophils and lymphocytes in women with SLE undergoing drug treatment, without ( n = 9) or with ( n = 5) 4 months of kinesiotherapy. Parameters related to functional capacity were also analyzed. In the case of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…These findings were in accordance with the results of Lamb et al for RA patients 6. Another important finding was that the exercise group presented a significant decrease of pain in all time points compared with control group, in accordance with the results of other studies in SLE patients26 or RA patients 27–29. However, some studies failed to present post-exercise decrease in pain in SLE patients30 and RA patients,31 32 likely due to different types of the exercise programme.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were in accordance with the results of Lamb et al for RA patients 6. Another important finding was that the exercise group presented a significant decrease of pain in all time points compared with control group, in accordance with the results of other studies in SLE patients26 or RA patients 27–29. However, some studies failed to present post-exercise decrease in pain in SLE patients30 and RA patients,31 32 likely due to different types of the exercise programme.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, these exploratory findings need to be assessed in detail in future studies. Despite of these results, flexibility has recently gained attention due to its potential role in cardiometabolic health [49] and pain reduction in SLE [19] and its inclusion in exercise programs is currently encouraged [50]. Future interventions studies are needed to examine these contradictory findings regarding flexibility and to determine the adequate regimes of intensity, frequency, and progression for possible health benefits in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to medical therapy, non-pharmacological therapies, such as exercise, seems to be an efficient and safe alternative to improve physical fitness [10], symptomatology and HRQoL of patients with SLE [11,12]. Aerobic training [1318], as well as strength and flexibility training [13,18,19] have shown a variable efficacy in improving diverse dimensions of HRQoL in SLE. Noteworthy, exercise interventions are typically poorly described and provide insufficient information to warrant replication and a clear understanding on how the different components of physical fitness must be trained along an intervention period for SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Perandini et al observed that a single bout (i.e., 30 min) of aerobic exercise (i.e., either at 50% or 70% of VO 2peak ) did not increase inflammation in women with either active or inactive SLE [22], and that 12 weeks of aerobic training ( n = 8) tended to reduce inflammation in comparison to a control group ( n = 10) [23]. Timoteo et al [24], however, did not observe changes in IL-6 or TNF-α in the combined exercise (i.e., flexibility, resistance and aerobic training) group ( n = 5) compared to the control group ( n = 9). Overall, these studies had a small sample size and the exercise programs were not comprehensively described to allow replication or application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%